Public Perceptions of the Ocean: Lessons for Marine Conservation From a Global Research Review - Jefferson, Rebecca; McKinley, Emma; Griffin, Holly; Nimmo, Alison; Fletcher, Stephen (Frontiers in Marine Science, 2021)
Insights into how public audiences perceive and relate to the ocean are pivotal to successful societal engagement and integration of human dimensions in marine conservation. Perceptions research explores how people understand, value or engage with an environment, issue or management response, and in the context of marine conservation, provides crucial insights for the development, delivery and evaluation of effective conservation interventions. This review of 349 peer reviewed studies explores the current state of research into public perceptions of the ocean. Using an extensive data extraction process, the review examined the geographical spread of ocean perceptions research, the topics of research focus, and the methods used. The review identifies gaps in current research activity, and opportunities for maximizing the impact of ocean perceptions research in current and future marine conservation. Key findings of the review include evidence that the rate of research is growing, with 59% of studies published between 2013–2017. However, a clear geographical skew is evident, with the majority of studies being undertaken in higher income countries. Furthermore, there has been a tendency to focus on charismatic species, or issues and spaces of clear human-ocean interaction (e.g., beaches), highlighting significant gaps in the topics and themes currently covered by ocean perceptions research. An additional gap identified is the underutilization of available methods to explore the complexity of marine perceptions. In a bid to address these gaps, the paper concludes with a series of recommendations designed to stimulate and support ocean perceptions research as being fundamental to the success of marine conservation efforts. While ocean perceptions research may be young, the growing research effort evidenced in this review gives optimism for realizing its potential and continuing to improve the integration of ocean perceptions research effectively into marine conservation.